Republic of Poland : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Alternate Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2019)
This 2018 Article IV Consultation discussions with the Republic of Poland focused on the strong growth upswing since 2017, which has been supported by three coincident cycles: a rebound in euro-area activity, a substantial increase in European Union transfers, and new large social benefit programs. It has been highlighted in the report that risks to the outlook for the Polish economy from external developments are elevated, while any slippage from prudent policies and sound governance principles could dent investors' risk appetite. Substantial adjustment in recent years has brought the medium-term objective within reach. Remaining adjustment should rely on sustainable, growth-friendly measures. The team recommended that independent and well-resourced financial supervision is essential for effective and even-handed oversight, particularly in a state-dominated financial system. Sustaining rapid income convergence as working-age population declines calls for durable increases in investment and productivity. Reforms should focus on removing existing barriers to investment, facilitating more reliable access to skilled labor, enhancing predictability of policy changes, and providing a level playing field for all investors by protecting the rights of minority shareholders and ensuring competition.